2023
DOI: 10.5093/pi2023a6
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of Meta-Analysis Data on Treatment Effectiveness for Physical, Psychological, and Sexual Intimate Partner Violence Perpetration

Abstract: Intimate partner violence can lead to physical, economical, mental, and sexual well-being issues, and even death, and it is most commonly experienced by women. There exist a number of treatment models for the prevention and treatment of intimate partner violence (IPV). In this study, we provided a comprehensive meta-regression analysis of the effectiveness of batterer treatment programs, with a view to characterizing the interplay between different forms of IPV (physical, psychological, and sexual). Using meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…In this special issue we aim to better understand the therapeutic needs, risk factors, and treatment resistance in IPV perpetrators to provide evidence-based responses to improve intervention programs. In the first manuscript of the special issue, Systematic investigation of meta-analysis data on treatment effectiveness for physical, psychological and sexual intimate partner violence perpetration, Ouztüzün et al (2023) found that differences in the effectiveness of perpetrator programs that may exist depending on the type of violence they are working with. Using meta-regression analysis, these authors assess the effects that different treatment models have on physical, psychological and sexual IPV.…”
mentioning
confidence: 99%
“…In this special issue we aim to better understand the therapeutic needs, risk factors, and treatment resistance in IPV perpetrators to provide evidence-based responses to improve intervention programs. In the first manuscript of the special issue, Systematic investigation of meta-analysis data on treatment effectiveness for physical, psychological and sexual intimate partner violence perpetration, Ouztüzün et al (2023) found that differences in the effectiveness of perpetrator programs that may exist depending on the type of violence they are working with. Using meta-regression analysis, these authors assess the effects that different treatment models have on physical, psychological and sexual IPV.…”
mentioning
confidence: 99%